Hobo Syndrome: A Cross-Organizational Mobility in Banking, Health and Development Sector - Tamkeen Saleem , Rehana Noor , Afsheen Jalil ,Shemaila Saleem (Journal of Rawalpindi Medical College, 2016)
Background: .This study examines the past quits and intentions to search for alternative jobs as predictor of Hobo Syndrome in Banking, Health and Development Sector. Methods: The sample consisted of 228 employees working in banking (n=76), health (n=76) and development (n=76) sector. The inclusion criterion for sample participation was at least 1 year of working experience in health, banking and development sectors. The selected organizations included private banks, hospitals and nongovernmental organizations.The age of the employees was ranging between 25 – 50 years. The intention to search for alternative job was measured. Question was anchored on a 5-point likert scale strongly disagree=1 and strongly agree=5. High scores indicate a strong urge to look for alternative job. Job Hopping Measure consisting of three items was used to gauge Hobo Syndrome. The responses were collected on scale format of 7-point Likert scale where strongly disagree= 1 to strongly agree= 7. 12For the analysis number of past quits was measured by the total number of times an individual had voluntarily exited a job as reported by the respondent. And frequency of past quits was also measured by likert format where never =1 and often= 4. Frequency of past quits was then used as a predictor of hobo syndrome. Reliability test was computed. Frequencies, custom tabulation and Regression analysis were used for analyses of the results. Results: The sector-wise past job quits are comparatively high in the bracket of 1-3 past job quits and here, job quitting seems high in health sector as compared to other sectors.The results also reveal that random job hopping is more prevalent than Strategic job hopping . Prevalence of frequent past job quits is higher in the early years of work experience as compared to employees with 7-10 years of experience. Cronbach Alpha for Intention to search for alternative job and Hobo Syndrome exhibits a good internal consistency . Intention to search for alternative job positively predicts Hobo Syndrome (F =189.59,p<.01). Intention to search for alternative job has a positive impact on Hobo Syndrome (=.83, p<.01) . The values of R2 of .48 indicates a 48% variance in the Hobo Syndrome by the predictor which is frequency of past quits (F =46.69,p<.01). Thus, frequency of past quitshas a positive impact on Hobo Syndrome (=.36, p<.01). Conclusion: The employees who search for new alternatives for job and display frequent job quits are more prone to demonstrate hoboness in their career.Historical analysis and biographical data to select workers should be employed to hire a consistent employee and to reduce cost of hiring frequently.